Modulation of chemical stability and in vitro bioaccessibility of beta-carotene loaded in kappa-carrageenan oil-in-gel emulsions. (1st April 2017) - Soukoulis, Christos; Tsevdou, Maria; Andre, Christelle M.; Cambier, Sébastien; Yonekura, Lina; Taoukis, Petros S.; Hoffmann, Lucien
Highlights: Ionically (Na +, Ca 2+, K + ) structured κ-carrageenan o/w emulsions were produced. Cation type and amount impacted β-carotene chemical stability and bioaccessibility. Ca 2+ presence and high ionic strength reduced chemical stability of β-carotene. Na + and K + o/g emulsions had higher β-carotene in vitro bioaccessibility. Ca 2+ presence influenced both colloidal and physical aspects of digesta. Abstract: In the present paper, ionotropically structured κ-carrageenan based oil-in-gel (o/g) emulsions were tested as potential carrier systems for the delivery of β-carotene. In situ ionic gelation was induced by Na +, K + or Ca 2+ added at the level of 0.2–0.6% (w/w). All o/g emulsions exerted a true gel like behaviour with storage modulus (G′) being reduced according to the order: K + >Ca 2+ >Na + . Ionic gelation induced a moderate increase in the microscopically assessed lipid droplets radii. O/g emulsions containing monovalent ions exerted the highest β-carotene retention throughout isothermal storage particularly at high (37 and 55 °C) temperatures. Notwithstanding, increasing ionic strength resulted in acceleration of β-carotene degradation rates for all cation species. β-Carotene bioaccessibility was significantly lower in Ca 2+ o/g emulsions due to the formation of complexes between the biopolymer matrix containing β-carotene and bile salts. A good correlation between β-carotene bioaccessibility, physical and colloidal aspects of the micellar digesta fractions was observed.